Implementasi Kebijakan Keterbukaan Informasi Publik (Studi Pemberdayaan dan Bantuan Sosial Pada Dinas Sosial Tenaga Kerja dan Transmigrasi Kabupaten Banggai Kepulauan) - Badalia, Fatri; Mandey, Jantje (JURNAL ILMU ADMINISTRASI (JIA), 2013)
Abstract: Less maximum dissemination and provision of information to the public related to the performance of labor and social services taransmigration Banggai archipelago in the management of data and information on empowerment and social assistance, it is in because of the limited resources that is owned by implementing policies in terms of both quality and quantity that affects the policy implementation process. lack of knowledge and insight into people's governance, especially the empowerment and social assistance, the maximum is less influenced by the provision of such information. The method used is descriptive qualitative research that describes the facts on the ground. Using data collection techniques, observation techniques, interviews, library research and documentation. The results showed that the public disclosure in view of three dimensions, namely, the ease of accessing the information, accurate and adequate information, the disclosure of information. Of the three dimensions, ease in obtaining the information are not enough in get by society, because human resources are owned by the apparatus implementing policies that are low or utilization of human resources have not been adequate. The conclusion that can pull in this study is that the public disclosure policy implementation has been accomplished, but not maximized, due to the utilization of human resources is not adequate in that agency. It is suggested that the government should undertake formal education. Keywords: public disclosure policy implementation, empowerment and social assistance